2006
DOI: 10.1111/j.1365-2915.2006.00636.x
|View full text |Cite
|
Sign up to set email alerts
|

Spatial and temporal distribution of bluetongue and its Culicoides vectors in Bulgaria

Abstract: Surveillance of Culicoides (Diptera: Ceratopogonidae) biting midges was carried out between 2001 and 2003, at 119 sites within a 50 x 50-km grid distributed across Bulgaria, using light trap collections around the time of peak adult midge abundance. Sentinel and ad hoc serum surveillance of hosts susceptible to bluetongue infection was carried out at around 300 sites between 1999 and 2003. Following the initial incursion of bluetongue virus 9 (BTV-9) into Bourgas province in 1999, affecting 85 villages along t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
46
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 51 publications
(49 citation statements)
references
References 30 publications
3
46
0
Order By: Relevance
“…Two epizooties of bluetongue virus (serotype 9) were observed in Bulgaria in 1999 and 2001 (Purse et al 2006). The following species are related to the bluetongue disease: Culicoides pulicaris complex, C. obsoletus complex and Monoculicoides group (see Appendix 1) (Nedelchev 2008).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Two epizooties of bluetongue virus (serotype 9) were observed in Bulgaria in 1999 and 2001 (Purse et al 2006). The following species are related to the bluetongue disease: Culicoides pulicaris complex, C. obsoletus complex and Monoculicoides group (see Appendix 1) (Nedelchev 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The following species are related to the bluetongue disease: Culicoides pulicaris complex, C. obsoletus complex and Monoculicoides group (see Appendix 1) (Nedelchev 2008). A survey focused on the culicoid vectors of BTV in Bulgaria (Purse et al 2006) revealed C. obsoletus complex as the most abundant followed by C. pulicaris complex; these two complexes represented 75% and 16%, respectively, of all individuals trapped, whereas, the major Old World vector, C. imicola, was not found. In our study, the representatives of subgenus Monoculicoides (C. puncticollis, C. nubeculosus and probably C. riethi) were the most abundant (33.48%) followed by the ornithophilic C. circumscriptus representing 31.30% of the insects sampled.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…More than 88% of all collections consisted of members of this sibling group, including C. obsoletus s.s. and C. dewulfi. Nine percent consisted of C. pulicaris, another species suspected as BTV vector Purse et al, 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Since then, BTV has spread into Mediterranean islands such as Corsica, Sicily and Sardinia. Recent BTV outbreaks in the Balkans are thought to have arrived from Asian Turkey and may be vectored by local vector species (Purse et al, 2006). Model predictions suggest a widespread distribution of BTV across the Mediterranean basin and into central Europe as far as southern Germany and Austria (Tatem et al, 2003;Wittmann et al, 2001).…”
Section: Introductionmentioning
confidence: 99%